1997
DOI: 10.1074/jbc.272.39.24154
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of Mitochondrial Respiratory Chain Complex III by Cell-permeable Ceramide

Abstract: Ceramide is a lipid second messenger that mediates the effects of tumor necrosis factor ␣ and other agents on cell growth and differentiation. Ceramide is believed to act via activation of protein phosphatase, prolinedirected protein kinase, or protein kinase C. Tumor necrosis factor ␣-induced common pathway of apoptosis is associated with an early impairment of mitochondria. Herein, we demonstrate that ceramide can directly inhibit mitochondrial respiratory chain function. In isolated mitochondria, a rapid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
300
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(318 citation statements)
references
References 34 publications
14
300
4
Order By: Relevance
“…Thus, Bcl-xL appears to account for at least a portion of sIg-induced Fas-resistance because, expression was upregulated coordinately with induction of Fas-resistance (in both murine and human B cells, reference [69]), and, because isolated overexpression diminished B cell susceptibility to Fas killing separate and apart from any other potential effects of sIg engagement (although in connection with this last point it should be mentioned that the capacity of Bcl-xL to inhibit Fas-mediated apoptosis in B cell lines has been questioned, reference [70]). Further, the reduction in susceptibility to Th1-induced cytotoxicity produced by Bcl-xL suggests that Fas death signaling in B cells involves mitochondrial cytochrome c release; this notion is supported by our observation that inducibly Fas-resistant B cells are protected against apoptosis produced by C2-ceramide, the cytotoxicity of which has been associated with mitochondrial damage [71][72][73][74][75][ [71][72][73][74][75].…”
Section: Two Terminal Effectors Of Fas-resistance: Bcl-xl and Flipmentioning
confidence: 54%
“…Thus, Bcl-xL appears to account for at least a portion of sIg-induced Fas-resistance because, expression was upregulated coordinately with induction of Fas-resistance (in both murine and human B cells, reference [69]), and, because isolated overexpression diminished B cell susceptibility to Fas killing separate and apart from any other potential effects of sIg engagement (although in connection with this last point it should be mentioned that the capacity of Bcl-xL to inhibit Fas-mediated apoptosis in B cell lines has been questioned, reference [70]). Further, the reduction in susceptibility to Th1-induced cytotoxicity produced by Bcl-xL suggests that Fas death signaling in B cells involves mitochondrial cytochrome c release; this notion is supported by our observation that inducibly Fas-resistant B cells are protected against apoptosis produced by C2-ceramide, the cytotoxicity of which has been associated with mitochondrial damage [71][72][73][74][75][ [71][72][73][74][75].…”
Section: Two Terminal Effectors Of Fas-resistance: Bcl-xl and Flipmentioning
confidence: 54%
“…22,23 The direct effect of ceramide on mitochondria was reproduced with GD3 ganglioside that leads to a marked loss of mitochondrial DCm and apoptosis. 24 These studies led us to assume that the mitochondrial dysfunction that we observed was not an artefact but was secondary to the GM3 synthase deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus nidulans, LCBs induce apoptosis associated with the accumulation of ROS, although ROS scavenging does not impair the induction of apoptosis (Cheng et al, 2003). In mammalian cells, ceramide has also been shown to increase the production of ROS, by directly inhibiting the mitochondrial complex III (Gudz et al, 1997) and via inhibition of Bcl2 mediated by the ceramide-activated protein phosphatase 2A (Ruvolo et al, 1999). The present study showed that Isc1p, the budding yeast neutral sphingomyelinase homologue, plays a key role in oxidative stress resistance and chronological lifespan.…”
Section: Discussionmentioning
confidence: 99%